MAKNA MENJADI GURU TAMAN KANAK-KANAK (Sebuah Studi Kualitatif Fenomenologis) - Putri Puspitarani; Achmad Mujab Masykur (Faculty of Psychology, Diponegoro University, 2018)
The Kindergarten teacher (TK) not only acts as an educator, but also the moral guardian of the students. Work as a kindergarten teacher is not easy, requires seriousness and patience to work with young children. This study aims to understand the process of interpreting the subject of his job as a kindergarten teacher from the beginning decided to become kindergarten teachers to find the meaning of being a kindergarten teacher. The research method used is qualitative method with phenomenological approach. Subjects in this study amounted to three people selected by purposive technique. Researchers determine the characteristics of the subject is a kindergarten teacher, has been teaching for more than ten years, working in private kindergarten, has attended teacher certification. Data collection was done by interview. The researcher uses data analysis expedition model, that is the process of expressing the subject which is still implied. The results showed that the three subjects interpreted positive work as a kindergarten teacher. The meaning of work in kindergarten teachers is influenced by the interaction between personal components, social components, spiritual components, and the value component (Bastaman, 1996). The intrinsic motivation of the three subjects gives satisfaction at work. The values gained from parents make the subject of never giving up on the challenges of the job. Subjects view the teacher is the embodiment of ideals, a fun job, calling the soul to educate the nation's children.